Preparing the future workforce for 2030: the role of higher education institutions - Pandya, Bharti; Ruhi, Umar; Patterson, Louise (Frontiers in Education, 2023)
The invasion of futuristic technologies has made it inevitable for the future workforce to confront this reality and be ready to work in the new world of work in 2030. Higher education institutions (HEIs) are obligated to assume a pivotal role in equipping students with the requisite competencies. Covid-19 has expedited the development process compelling HEIs to make a mega shift to prepare the future workforce. Primary data was collected from HEI students across 11 countries to analyse their confidence to work in the new world of work in 2030 and to understand the role of HEIs in influencing students' confidence. Exploratory Factor Analysis (EFA) and Partial Least squares (PLS) based structural equation modelling (SEM) procedures were employed to estimate a structural model of awareness and readiness (cognitive) and confidence (affective) factors, and the combined effect of HEI, awareness, and readiness on overall student confidence in their knowledge, skills and abilities. The statistical results indicate that there are strong significant relations between the HEI-Awareness; HEI-Awareness-Confidence; HEI-Readiness; and HEI-Readiness-Confidence and these dependencies are not just by chance. The results of this research are significant for higher education policy developers and curriculum developers to incorporate future competencies in the program. Further, educators and researchers will benefit from the results to develop teaching strategies and content to equip the future workforce for 2030.et